2020
DOI: 10.1038/s41467-020-16029-7
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing controls teneurin-latrophilin interaction and synapse specificity by a shape-shifting mechanism

Abstract: The trans-synaptic interaction of the cell-adhesion molecules teneurins (TENs) with latrophilins (LPHNs/ADGRLs) promotes excitatory synapse formation when LPHNs simultaneously interact with FLRTs. Insertion of a short alternatively-spliced region within TENs abolishes the TEN-LPHN interaction and switches TEN function to specify inhibitory synapses. How alternative-splicing regulates TEN-LPHN interaction remains unclear. Here, we report the 2.9 Å resolution cryo-EM structure of the TEN2-LPHN3 complex, and desc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(113 citation statements)
references
References 64 publications
(97 reference statements)
6
100
1
Order By: Relevance
“…Cirl is the Drosophila homolog of vertebrate latrophilin, a member of the adhesion GPCR (aGPCR) subfamily ( Scholz et al., 2015 ; Schöneberg and Prömel, 2019 ). Interestingly, the Toll-8 extracellular domain shares sequence similarities with that of the human LRR protein FLRTs ( Dolan et al., 2007 ), which are known to form protein complexes with human latrophilins ( Boucard et al., 2014 ; Li et al., 2020 ; O’Sullivan et al., 2012 ; Sando et al., 2019 ; del Toro et al., 2020 ). We also recovered Toll-2 as a significant Toll-8-binding partner in vivo ( Figure 3 B; Table S1 ), in agreement with previous findings in vitro ( Paré et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cirl is the Drosophila homolog of vertebrate latrophilin, a member of the adhesion GPCR (aGPCR) subfamily ( Scholz et al., 2015 ; Schöneberg and Prömel, 2019 ). Interestingly, the Toll-8 extracellular domain shares sequence similarities with that of the human LRR protein FLRTs ( Dolan et al., 2007 ), which are known to form protein complexes with human latrophilins ( Boucard et al., 2014 ; Li et al., 2020 ; O’Sullivan et al., 2012 ; Sando et al., 2019 ; del Toro et al., 2020 ). We also recovered Toll-2 as a significant Toll-8-binding partner in vivo ( Figure 3 B; Table S1 ), in agreement with previous findings in vitro ( Paré et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Current structural information of adhesion GPCRs is limited to views of extracellular portions of the receptor including GAIN domains, the GAIN plus adjacent NTF subdomains, or for ADGRG1, the entire NTF (5,13,72,96). If the ECRs or NTFs of adhesion GPCRs parallel the function of Family B1 ECDs, then they may bind the ECLs and act to constrain the 7TM bundle in a low activity state (Fig.…”
Section: Class B1 Gpcr Activating Transitions and Peptide Agonism: Pamentioning
confidence: 99%
“…ADGRL receptors bind to three classes of single-membrane pass, transpresented protein ligands: teneurins, neurexins, and FLRTs. Teneurins bind to the ADGRL Lec domain, while neurexins and FLRTs interact with the ADGRL Olf domain (82,96,114,121). These proteins comprise trans-synaptic signaling complexes and provide models for understanding how AGPCRs can be activated by trans-presented ligands.…”
Section: Trans-cell-presented Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lphn2 is enriched in stratum lacunosum moleculare and required for the targeting of entorhinal cortex inputs to distal dendrites, while Lphn3 is enriched in both CA1 stratum radiatum and stratum oriens and is required for the targeting of those layers by Schaffer collateral axons from CA3 and commissural fibers from the contralateral hippocampus (Figure 6A; Anderson et al, 2017;Sando et al, 2019). Subsequent structural studies have shown that this mechanism relies on heterotrimeric transsynaptic binding complexes, and that synapse formation relies on GPCR intracellular signaling (Del Toro et al, 2020;Li et al, 2020b;Sando and Südhof, 2021). These results agree in general with other studies of the hippocampus highlighting the roles of selectively distributed transmembrane molecules in generating laminar or subcellular-domain-specific synaptic targeting.…”
Section: Mechanisms For Targeting Excitatory Input To Subcellular Domains Of Pyramidal Neuronsmentioning
confidence: 98%